Oviposition Preference of the Japanese Beetle (Coleoptera: Scarabaeidae) in Golf Putting Greens under Different Soil Moisture and Fungicide Regimes. Issue 1 (10th January 2014) - Obear, Glen R.; Williamson, R. Chris; Liesch, P. J.
Abstract : Larvae of the Japanese beetle, Popillia japonica Newman (Coleoptera: Scarabaeidae), are rarely found in golf course putting greens despite seemingly ideal characteristics. Sand‐based putting green root zones are often maintained at relatively low volumetric water contents that could be unsuitable for survival of P. japonica eggs or larvae. Putting greens also receive frequent applications of fungicides throughout the growing season, and it is possible that these chemicals deter females from laying eggs. This study was conducted to determine how the volumetric water content of sand putting green soils and the application of the fungicide active ingredients propiconazole and chlorothalonil affect the oviposition (i.e., egg laying) behavior of the Japanese beetle. In a soil moisture choice assay, adult females avoided investigating (i.e., digging) in soils maintained just above the wilting point of the turfgrass (∼5% volumetric water content). In another experiment, neither the application of propiconazole nor chlorothalonil had any effect on female investigation. Recovery of larvae was low in both assays, possibly due to the coarse texture of the sandy soils used in these studies. These findings suggest that conservative irrigation could lessen infestations of P. japonica, and that single applications of propiconazole or chlorothalonil do not affect female oviposition choice.